A Diagnostic Challenge of Ulcerative Lesion over the Tongue - Ansari, Ashfaque; Bavisetty, L. V. Manjusha (New Advances in Medicine and Medical Science Vol. 4, 2023)
This case highlights the importance of considering TB in the differential diagnosis of non-healing ulcers of the tongue in India, particularly in immune-compromised individuals and HIV patients. Tuberculosis is caused by Mycobacterium tuberculosis, It remains the most common infectious disease affecting the lungs in India to date, and can present with various extrapulmonary manifestations. One rare manifestation of TB is tuberculosis of the tongue, which is often misdiagnosed as malignant lingual neoplasms. In this case, we present a 69-year-old patient with TB of the tongue, who presented with a chronic painful non-healing ulcer, so far very few cases reported.